Kacamata Sensor Jarak untuk Penyandang tunanetra sebagai Implementasi Nilai Keadilan Sosial bagi Seluruh Rakyat Indonesia - Basuki, Cahyo (Journal of Innovation and Applied Technology, 2026)
People with visual impairments in Indonesia have not yet been matched by adequate public facilities to support their daily social activities. This condition reflects a sub-optimal implementation of the fifth principle of Pancasila, namely Keadilan Sosial bagi Seluruh Rakyat Indonesia. Currently, the conventional white cane is only capable of detecting obstacles on the ground surface within a limited range. This article aims to design smart glasses based on ultrasonic distance sensors as an alternative solution to assist visually impaired individuals in detecting obstacles more effectively. Using a descriptive qualitative method, the results indicate that ultrasonic sensor glasses have the potential to help visually impaired users identify obstacles at a certain distance more efficiently compared to conventional white canes. Therefore, this innovation is expected to support their right to social justice in terms of public accessibility.